Analisis Kesiapsiagaan Kedaruratan K3 Dalam Meningkatkan Keselamatan dan Kesehatan Kerja di Industri Konstruksi - Elsa Alelga; Rizka Tiara; Abdurrozzaq Hasibuan (PT. Alahyan Publisher Sukabumi, 2024)
Emergency preparedness in Occupational Health and Safety (OHS) plays a crucial role in the construction industry to reduce accidents and ensure worker well-being. This research aims to analyze the factors influencing OHS emergency preparedness and strategies to enhance it. A literature review method was used to identify best practices and the role of government regulations. The results indicate that training, evaluation, technology, and regulations have a significant impact on OHS emergency preparedness in the construction industry